The Dose Distribution from Iridium-192 Source on Cervical Cancer Brachytherapy by Manchester System Using Monte Carlo Simulation - F. Kurniati; F. P. Krisna; J. Junios; F. Haryanto (Atom Indonesia, 2021)
One treatment for cervical cancer is to use radioactive sources that directly target the cancer cell called brachytherapy. This study is aimed to determine dose distribution at phantom pelvis using the DOSXYZnrc Monte Carlo code. The phantom was derived from a CT scan image of the DICOM-type pelvis with a size of 50 × 50 × 28.8 cm obtained from Santosa Kopo Hospital. The source used was Ir-192, which makes an asymmetrical beam with a size of 0.45 × 0.09 × 0.09 cm. Monte Carlo simulation was performed to determine the dose distribution of the Ir-192 source on cervical cancer CT images based on the Manchester system. The Monte Carlo simulation was divided into two models with distance variations on the applicator. Model A used TPS data with a distance between sources of 0.9 cm, while model B had a distance between sources of 0.5 cm. The distribution of dose resulting from the Monte Carlo simulation was analyzed and compared with TPS data. The results showed that at the range of 50 %, dose distribution in model A reaches the end of 3.9 cm. When compared to the range of 50 % dose distribution at the TPS results that reaches the point of 4 cm, it produces a deviation value of 2.5 %, which is still within the tolerance range. Model A and Model B provide different dose distribution. In model B, it reaches 3.86 cm, resulting in a deviation of 1.02 %, which is still within the tolerance range. The resulting γ-index value for the 50 % dose distribution was 2.26, while the whole area's GPR value was 94.13 %. This indicates a difference in dose distribution between the two models. Therefore, the smaller the distance between the sources, the shorter the dose distribution range with relatively more uniform dose distribution.